PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN TERHADAP PRODUKTIVITAS PERTANIAN DI KABUPATEN MANGGARAI BARAT - Daru, Geronsius Sangsun Deo Datus; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 12 (2022): Vol.11.12. DESEMBER 2022[4234-4463]DO - 10.24843/EEP.2022.v11.i12.p03, 2022)
Indonesia's infrastructure development through the road construction program. This study uses panel data, the number of observations in this study is 192 observation points. The data used is secondary data with data collection methods, namely non-participant observation. The data collected was then analyzed using panel data regression analysis techniques. The results of the research on the effect of the construction of hotmix road infrastructure, asphalt road infrastructure, gravel road infrastructure, dirt road infrastructure, good road infrastructure, medium road infrastructure, damaged road infrastructure, and heavily damaged road infrastructure on agricultural productivity in West Manggarai Regency show a relationship or no effect. The period of leadership that influenced the high and low agricultural productivity in West Manggarai Regency. Keywords: Road Infrastructure, Road Infrastructure According Conditions, Harvested Area, Food Production Results, Agricultural Productivity